(untitled) (Marketing Journal, 2025)
This article examines the effectiveness of using foreign experience in attracting investment to the agricultural sector of Uzbekistan and its impact on subsequent economic growth. It examines how the adaptation of successful international investment practices, such as tax incentives, the establishment of free economic zones, and comprehensive regulatory reforms, has significantly increased the flow of foreign direct investment. The article analyzes the mechanisms for integrating these foreign experiences in to Uzbekistanʼs economic policy and their measurable contribution to 22 economic development, employment growth, and the modernization of agricultural production.